Performance Analysis of Authentication Mechanism in Microservice - Mat Ghani, Muhammad Izzat Faris (IRC, 2020)
Performance is a factor that system designers need to consider when designing microservice. There are many key elements that could affect the performance of a microservice application. For example, communication protocol used between services or network latency. Sometimes it is hard to pinpoint exactly which part of a microservice is causing a performance bottleneck. In order to explore factors affecting performance in a microservice application, this research had benchmarked the performance of a microservice application, developed using 2 different authentication mechanism. The first version is an implementation using distributed session store, and the second version is an implementation using JSON Web Token (JWT). Both implementations had been benchmarked by performing load testing to evaluate and compare their performance.